Three-dimensional momentum imaging of dissociation in flight of metastable molecules - Jochim, Bethany; Erdwien, Reid; Malakar, Y.; Severt, T.; Berry, Ben; Feizollah, Peyman; Rajput, Jyoti; Kaderiya, B.; Pearson, W. L.; Carnes, K. D.; Rudenko, A.; Ben-Itzhak, I. (My University, 2017)
We investigate dissociation in flight of metastable molecular dications formed by ultrashort, intense laser pulses using the cold target recoil ion momentum spectroscopy technique. A method for retrieving the lifetime(s) of the transient metastable state(s) as well as the complete three-dimensional momenta of the dissociating fragments is presented. Specifically, we demonstrate and discuss this approach by focusing on dissociation in flight of the ethylene dication going to the deprotonation channel. Two lifetimes are found to be associated with this process, C2H C2H3+ + H+: ns and ns. For the corresponding channel in deuterated ethylene, lifetimes of ns and ns are obtained.